Minds vs Machines: Historical and logical-philosophical review of the Lucas-Penrose’s Gödelian argument - Gherab, Karim (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper presents, from a historical and logical-philosophical perspective, the Gödelian arguments of two Oxford scholars, John Lucas and Roger Penrose. Both have been based on Gödel's Theorem to refute mechanism, computationalism and the possibility of creating an AI capable of simulating or duplicating the human mind. In the conclusions, the growing application of empirical methods in mathematics is mentioned and a possible path that would support Lucas and Penrose's arguments is speculated.